1981
DOI: 10.1021/ac00225a023
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ionic species by fulvic acid

Abstract: Studies have shown that a fuivic acid derived from soil is capable of reducing Hg(II) to Hg(0), Fe(III) to Fe(II), and I2 and I3" to under conditions generally characteristic of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(119 citation statements)
references
References 37 publications
5
113
0
1
Order By: Relevance
“…Furthermore, one can notice that there is a marked difference between the experimental data form different authors for uranium (VI) under low CO 2 (g) partial pressure. 14 Nevertheless, in the case of uranium, neither the results of Li et al [102], nor those from Artinger et al [26] could be assessed by this exercise. In the latter study, the authors did not observe any difference in the behaviour of uranium, introduced as uranium (VI) or uranium (IV), neither with purified HA [102], nor with Gorleben groundwater in the presence of natural organic matter at varying E H [26].…”
Section: Application To Redox Sensitive Actinide Elementsmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, one can notice that there is a marked difference between the experimental data form different authors for uranium (VI) under low CO 2 (g) partial pressure. 14 Nevertheless, in the case of uranium, neither the results of Li et al [102], nor those from Artinger et al [26] could be assessed by this exercise. In the latter study, the authors did not observe any difference in the behaviour of uranium, introduced as uranium (VI) or uranium (IV), neither with purified HA [102], nor with Gorleben groundwater in the presence of natural organic matter at varying E H [26].…”
Section: Application To Redox Sensitive Actinide Elementsmentioning
confidence: 92%
“…Experimental difficulties have often prevented from obtaining reliable results on reduced states of uranium, neptunium or plutonium. Furthermore, the redox properties of humic substances [3][4][5] have led to confusing results for protactinium [6], neptunium [7,8], plutonium [9][10][11][12] and other elements [13][14][15][16][17][18][19], even if the use of ligands to stabilise redox state is well known in the nuclear industry [20][21][22][23]. Otherwise, the reduction of uranium (VI) by HS has not been clearly observed up to now [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium is likely to be in the measurable form H 2 VO − 4 in the pH range 5-9 and the E h (redox potential) range 0-1 V. [9] Reduction of V V to V IV can occur with organic materials as electron donors, [10,11] with reduction to V III requiring a stronger reductant. V III is rapidly hydrolysed in aqueous solution, resulting in the precipitation of relatively insoluble V III oxyhydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, due to its highest total acidity which is highest than the other fractions of humic substances, FA is chosen to coat Fe3O4 and the formed Fe3O4-FA is then applied to adsorp [AuCl4] -in aqueous solution [28]. Skogerboe and Wilson [28] reported that fulvic acid had reduction potential approximately 0.5 V (vs normal hydrogen electrode), while the reduction potential of [AuCl4] -is 0.1 V. Its means, reduction of [AuCl4] -into Au(0) occur spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Skogerboe and Wilson [28] reported that fulvic acid had reduction potential approximately 0.5 V (vs normal hydrogen electrode), while the reduction potential of [AuCl4] -is 0.1 V. Its means, reduction of [AuCl4] -into Au(0) occur spontaneously. Higher total acidity needed in purpose to increase Fe3O4 stability.…”
Section: Introductionmentioning
confidence: 99%